Math

f(x)=13x^2 -15x-14
g(x)=15x^3+14x^2-15x+12
find f(3) × f(10) + f(-7) × g(9)

asked by Miley
  1. see

    http://www.jiskha.com/display.cgi?id=1388190290

    posted by Steve

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(9)
  2. Algebra

    I need help trying to put the correct vocabulary words when solving this problem such as grouping, factor, prime factor, GCF, and perfect square, and please check and see if I am doing this correctly. 15x^2+31x+2 In my last
  3. Algebra

    I need help trying to put the correct vocabulary words when solving this problem such as grouping, factor, prime factor, GCF, and perfect square, and please check and see if I am doing this correctly. 15x^2+31x+2 In my last
  4. math

    Solve by elimination 5x+y=2 3x+y=1 This is what I got : 3(5x+y=2) -5(3x+y=1) 15x+3y=6 -15x-5y=-5 -2y=1 2 2 Y=1/2 15x+3(1/2)=6 15x+3/2 =6 15x/15= 9/2 /15 X=3/10
  5. Math?

    Which expression is equivalent? −5(−3x − 6) A) 15x + 30 B) 15x − 30 C) −15x + 30 D) −15x − 30
  6. Math

    Ms.lynch has 21 coins in nickles and dimes.Their total value is $1.65. How many of each coin does she have? 21 - ( 0.05x + 0.10x)=1.50 21- 0.15x = 1.50 0.15x=21-1.50 0.15x=19.5 ------ 0.15 = 19.5/ 0.15 x=130 ??????
  7. Math to hard please help

    Add or subtract (4x^2+15x-3)-(3x^2+5) A. 7x^2+15x-8 B. x^2+12x+2 C. x^2+15x-8 D. 7x^2+8 Please help me. Thanks
  8. algbrea

    3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -28 = 2x -12 -28 =x -40 =x 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -10x+35=63 -10x=28 x=-2.8 you are both wrong! 3x - 15x + 35 = 2x + 18 +
  9. Math

    William solves the equation 5(3x-2)=15x-2. How many solutions does he find? A.0 solutions B.1 solution C.2 solutions D.Infinitely many solutions I'm only up to making it to: 15x-10= 15x-2 I was also wondering if I did anything
  10. Algebra 1b!

    1. Find the excluded value of x for the polynomomial expression 4x/6 a. 6 b. -6 c. 1/6 d. -1/6 2. Simplifly 3-2x/7 + 4x+5/7 a. 2x+8/14 b. 2x+8/7 <--- c. x+1/7 d. 2x+2/7 3. Simplify 6ab^6/4a^7b^10 * a^3b^4/2a^7b^6 a. 7x/8 - 2x/8

More Similar Questions